FAKTOR-FAKTOR PENYEBAB IBU RUMAH TANGGA BEKERJA SEBAGAI PEMECAH BATU SUPLI (STUDI DESA KONTUNAGA KECAMATAN KONTUNAGA KABUPATEN MUNA) - Irwan, Irwan; Peribadi, Peribadi; Tuwu, Darmin (Universitas Halu Oleo, 2022)
This study aims to find out what is the background of housewives working as stone crushers in Kontunaga Village, Kontunaga District, Muna Regency. This research is a descriptive research with a qualitative approach. Data collected through interview and documentation techniques with research informants as many as 15 people. The results of this study indicate that the factors that influence housewives to work as stone-breakers are due to meet the economic needs of the family. This is because of the condition of the household in that layer that requires a double source of income if only from the income of the father or head of the household. So with that women who work to earn a living as stone-breakers in Kontunaga village, have a positive role and impact in increasing family income, so that they can meet the needs of family life both clothing, food, shelter, and tertiary needs such as education for children, health. family and other urgent or unexpected matters.